Risk of hypothyroidism among patients with nasopharyngeal carcinoma treated with radiation therapy: A Population-Based Cohort Study. Issue 3 (June 2017) - Fan, Chao-Yueh; Lin, Chun-Shu; Chao, Hsing-Lung; Huang, Wen-Yen; Su, Yu-Fu; Lin, Kuen-Tze; Tsai, I-Ju; Kao, Chia-Hung
Abstract: Background and purpose: This study aimed to assess the incidence and risk of hypothyroidism among patients with nasopharyngeal carcinoma (NPC) after radiation therapy (RT). Material and methods: We identified 14, 893 NPC patients and 16, 105 other head and neck cancer (HNC) patients treated with RT without thyroidectomy from the National Health Insurance Research Database in Taiwan between 2000 and 2011. Each NPC patient was randomly frequency-matched with four individuals without NPC by age, sex, and index year. Competing-risk regression models were used to estimate hazard ratios (HRs) of hypothyroidism requiring thyroxin associated with NPC after RT. Results: The risk of developing hypothyroidism was significantly higher in the NPC cohort than in the matched cohort (adjusted HR = 14.35, 95% CI = 11.85–17.37) and the HNC cohort (adjusted HR = 2.06, 95% CI = 1.69–2.52). Independent risk factors for hypothyroidism among NPC patients included younger age, female sex, higher urbanization level, autoimmune disease, and receipt of chemotherapy. Conclusion: The risk of hypothyroidism requiring thyroxin was significantly higher in NPC patients after RT than in the general Taiwanese population and HNC patients. Regular clinical and serum thyroid function tests are essential among NPC survivors after RT.